Aerosol jet printed AgNW electrode and PEDOT:PSS layers for organic light-emitting diode devices fabrication - Hamjah, Mohd Khairulamzari; Steinberger, Marc; Tam, Kai Cheong; Egelhaaf, Hans Joachim; Brabec, Christoph; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
Aerosol jet printing is a cutting-edge technology offering a plethora of advantages in organic optoelectronics fabrication. In this work, we fabricated organic light-emitting diodes on glass substrates. Silver nanowires (AgNWs) and poly (3,4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS) were aerosol-jet printed as the bottom electrode and hole transport layer, respectively. The other remaining layer materials were blade coated to form a multi-layered structure of the devices. The results show that the organic lightemitting diode device with 40 mm2 active areas was successfully obtained. A comparison study of blade-coated organic light-emitting diode devices on indium tin oxide based electrode is also discussed. The results of this work show that aerosol jet printing technology enables fully solution-based fabrication of organic light-emitting diode devices.
CRIS-Team Scopus Importer:2021-04-02
Keywords: 4-ethylene dioxythiophene) polystyrene sulfonate; aerosol jet printing; organic light-emitting diode; poly(3; silver nanowires

Aerosol Jet Printing of Polymer Optical Waveguides - Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Lorenz, Lukas; Franke, Jörg (Springer International Publishing, 2022)
This research presents an advanced fabrication process of aerosol jet printed polymer optical waveguides onto 2D and 3D surfaces. The key advantage of the aerosol printed polymer optical waveguides is the capability of the process to print directly on desired surfaces, which significantly reduced the cost for new/customization production. Comprehensive studies of the optical material selection, printing strategies, printing process optimization and quality characterization of the printed polymer optical waveguide are successfully conducted. With the optimum printing process, the desired aspect ratio of the polymer optical waveguides is obtained at the height to width ratio ofâ€‰ â€‰1:5 and contact angle ofâ€‰ â€‰45° to 60°. Optical analysis of the printed polymer optical waveguide samples record attenuation rates up to 0.2 dB/cm and transmission rates of 10 Gbit/s. These significant achievements are likely to become a game-changer to the existing metallic conductor.
CRIS-Team Scopus Importer:2024-12-16

Feasibility of Printed Optical Waveguides Over the Entire Process Chain by OPTAVER - Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Zeitler, Jochen; Franke, Jörg; Lorenz, Lukas; Bock, Karlheinz; Backhaus, Carsten; Loosen, Florian; et al. (Springer International Publishing, 2022)
The integration of the knowledge of different engineering disciplines to build a three-dimensional optical short-range interconnect system is the core of this book. For this purpose, the physical and technological principles of optical technologies have to be considered. The focus here is on optical transmission technology. Attenuation, the propagation of optical signals, the construction of printed optical waveguides and their manufacturing processes play a special role. Likewise, product development methods of technical systems are a related field; since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these have to be evaluated and expanded with regard to the new optomechatronic components.
CRIS-Team Scopus Importer:2024-12-16

Machine Learning Approach towards Quality Control of Aerosol-Jet Printed Polymer Optical Waveguides Material - Hamjah, Mohd Khairulamzari; Thielen, Nils; Hagelloch, Jan Erik; Franke, Jörg (TENSYMP 2021 - 2021 IEEE Region 10 Symposium, 2021)
In this work, a Machine Learning approach to predict the quality of the aerosol jet printed polymer optical waveguides material is presented. For the acquisition of necessary data, a video camera system was integrated into the aerosol jet printing. An image processing tool was developed to extract printed line width and to map to the process data of the printing. For modeling, an Automated Machine Learning framework was utilized to reduce development time for a proof of concept. The final ML model reached R2 score of 74 % in predicting line width and surpassed the statistical approaches.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Aerosol jet printing; Machine Learning; polymer optical waveguides

Manufacturing of Polymer Optical Waveguides for 3D-Opto-MID: Review of the OPTAVER Process - Hamjah, Mohd Khairulamzari; Zeitler, Jochen; Eiche, Yannic; Lorenz, Lukas; Backhaus, Carsten; Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Lindlein, Norbert; Bock, Karlheinz; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
In order to meet the increasing demand for data transmission over short distances of up to 100 m, the Optical Assembly and Connection Technology for ComponentIntegrated Bus Systems (OPTAVER) research group, funded by the German Research Foundation (DFG), developed a process for the additive manufacturing of three-dimensional optical waveguides. The research group focuses on design and modeling, simulation, and manufacturing polymer optical waveguides to produce 3D-Opto-Mechatronic-Integrated Devices (3D-Opto-MID). Inside 3D-Opto-MID, an optical coupler is presented based on an asymmetrical coupling principle. This paper reviews the entire process chain and the corresponding research results of the OPTAVER process.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 3D-Opto-MID; aerosol jet printing; asymmetrical optical bus coupling; flexographic printing; functionalization; printed multimode waveguides; Raytracing; wave propagation method

Reliability of 3D-Opto-MID Packages for Asymmetric Optical Bus Couplers - Lorenz, Lukas; Hanesch, Florian; Nieweglowski, Krzysztof; Hamjah, Mohd Khairulamzari; Franke, Jörg; Hoffmann, Gerd-Albert; Overmeyer, Ludger; Bock, Karlheinz (IEEE 71ST ELECTRONIC COMPONENTS AND TECHNOLOGY CONFERENCE (ECTC 2021), 2021)
CRIS-Team WoS Importer:2021-10-29